Family members' knowledge, attitudes, practices, and caregiver burden in managing the health of patients with severe burn injuries - Wang, Huili; Yang, Jiaming; Xia, Mengjia; Zhu, Linying; Liao, Mirong (Frontiers in Public Health, 2025)
BackgroundCaregivers, particularly family members, play a vital role in the treatment and recovery of burn patients, yet their psychological burden and care competency are often overlooked. Despite their crucial role, there is limited research examining their knowledge, attitudes, and practices in burn care management.ObjectiveThis study aimed to investigate knowledge, attitudes, practices (KAP), and burdens experienced by family members in managing the health of patients with severe burn injuries.MethodsA cross-sectional study was conducted at Zhejiang Province, from November 1, 2023, to January 31, 2024. Data were collected using a self-administered KAP questionnaire and Zarit Caregiver Burden Scale 12-item Short Form.ResultsThe study enrolled 459 valid participants, of which 253 (55.12%) were female. Median scores [25th percentile, 75th percentile] for knowledge, attitude, practice, and caregiver burden were 12 [9, 14], 17 [16, 19], 33 [31, 37], and 16 [10, 23], respectively. Correlation analysis revealed that higher caregiver knowledge was associated with improved attitudes (r = 0.35, P < 0.001) and more proactive practices (r = 0.36, P < 0.001), while being inversely related to caregiver burden (r = −0.18, P < 0.001). Better attitudes strongly predicted enhanced practices (r = 0.75, P < 0.001) and reduced caregiver burden (r = −0.24, P < 0.001). Similarly, more proactive practices were associated with lower caregiver burden (r = −0.25, P < 0.001). Multivariate logistic regression analysis identified that income levels of 5,001–10,000 Yuan (OR = 12.6, 95% CI: [2.57, 62.4], P = 0.002) and 10,001–20,000 Yuan (OR = 8.05, 95% CI: [1.53, 42.3], P = 0.014) were found to be independently associated with increased caregiver burden.ConclusionThe study demonstrates that while family members generally hold positive attitudes and are proactive in the care management of patients with severe burn injuries, their knowledge levels remain suboptimal, and they experience a mild to moderate caregiver burden. Structured caregiver education programs focusing on long-term burn complications and psychological support should be implemented to enhance care quality and reduce caregiver burden.